Sleep disordered breathing: prevalence and association with cardiovascular disease in the French general population. (25th November 2020) - Balagny, P; Wiernik, E; Matta, J; Frija-Masson, J; Vidal-Petiot, E; Steg, P.G; Ribet, C; Goldberg, M; D'Ortho, M.P; Zins, M
Abstract: Background: Sleep Disordered Breathing (SDB) is highly prevalent and associated with cardiovascular disease (CVD) but many studies have a limited sample size or uncertain generalizability. Purpose: The aim of this study was to obtain contemporary data on SDB prevalence and to assess its impact on CVD occurrence in a large French population-based sample. Methods: Data came from participants of the French population-based CONSTANCES cohort, included between 2012 and 2016, with clinical interview, examination and standard biology at inclusion and who were screened for SDB in 2017 using the Berlin Questionnaire (BQ). Follow-up was performed through yearly CONSTANCES questionnaires. CVD occurrence was defined by self-declared myocardial infarction or stroke between 2013 and 2017. Exposure variables were SDB diagnosis on the basis on BQ and its related sleeping symptoms (snoring, apnea and sleepiness). Odds Ratios (OR) were computed with their 95% Confidence Interval (95% CI) and adjusted for age, sex, smoking, dyslipidemia, diabetes, hypertension and body mass index (except for SDB since BQ considers these variables). Results: Among 54 228 participants, SDB prevalence was 16.1%. Over four years of follow-up, CVD occurred in 2.23% of SDB participants vs 0.72% in non SDB (OR=1.72, 95% CI [1.41–2.09]). CVD occurrence did not increase significantly with snoring (OR=0.95, 95% CI [0.78; 1.17]), but with apnea (OR=1.34, 95% CI [1.05; 1.71]) and with sleepiness (OR=1.42, 95% CI [1.18–1.72] when fatigue occurred after-sleep and OR=1.62, 95% CI [1.33–1.97] during waking time). These associations remained non-significant for snoring regardless of its frequency or noise, were significant for sleepiness as soon as it happened at least once a week and tended to increase with its frequency whenever fatigue occurred (p for trend<0.001). Subgroups analysis in hypertensive and non-hypertensive participants found similar results concerning snoring and sleepiness. Conclusions: These results confirm that SDB is highly prevalent in the general French population and is associated with a higher occurrence of CVD particularly in sleepy and apneic subjects. Screen for SDB and its symptoms should be relevant to identify high cardiovascular risk people who would benefit from preventive measures. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Plan d'Investissement d'Avenir-3 (PIA3-RHU, Ministry of Health)